Deep hypothermic extracorporeal membrane oxygenation cannula exchange in a child with necrotic pneumonia. (March 2020) - Martens, Thomas; Saini, Rajan; Crook, Richard; Robertson, Alex; Muthialu, Nagarajan; Brown, Katherine
Necrotizing pneumonia can lead to respiratory insufficiency in previously healthy children. Extracorporeal membrane oxygenation can be used for hemodynamic salvage and subsequent lung rest awaiting recovery. We present a case of a child initially placed on veno-arterial extracorporeal membrane oxygenation and converted to veno-venous extracorporeal membrane oxygenation. This was done under deep hypothermia in the operating theater.